2020
DOI: 10.1080/21645515.2020.1733869
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of a quadrivalent meningococcal tetanus toxoid-conjugate vaccine (MenACYW-TT) in healthy toddlers: a Phase II randomized study

Abstract: Neisseria meningitidis can lead to invasive meningococcal disease to which young children are particularly vulnerable. We assessed the immunogenicity and safety of Sanofi Pasteur's investigational quadrivalent (serogroups A, C, Y, and W) meningococcal tetanus-toxoid conjugate vaccine, MenACYW-TT, as a single dose, in healthy meningococcal vaccine-naïve toddlers versus a licensed conjugate vaccine MCV4-TT (NCT03205358). In this Phase II study conducted in Finland, 188 toddlers aged 12-24 months were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
(35 reference statements)
1
29
0
4
Order By: Relevance
“…This study did not assess the levels of anti-carrier antibodies, tetanus in the case of MenACYW-TT, however, a phase II study of MenACYW-TT has shown an increase in anti-tetanus antibody levels following vaccination. 21 This study offers key data about the safety and immunogenicity profile of the MenACYW-TT conjugate vaccine when administered as a booster in an MCV4-primed population. The data strongly support MenACYW-TT conjugate vaccine as an effective booster vaccination, regardless of the type of MCV4 administered for priming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not assess the levels of anti-carrier antibodies, tetanus in the case of MenACYW-TT, however, a phase II study of MenACYW-TT has shown an increase in anti-tetanus antibody levels following vaccination. 21 This study offers key data about the safety and immunogenicity profile of the MenACYW-TT conjugate vaccine when administered as a booster in an MCV4-primed population. The data strongly support MenACYW-TT conjugate vaccine as an effective booster vaccination, regardless of the type of MCV4 administered for priming.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not assess the levels of anti-carrier antibodies, tetanus in the case of MenACYW-TT, however, a phase II study of MenACYW-TT has shown an increase in anti-tetanus antibody levels following vaccination. 21 …”
Section: Discussionmentioning
confidence: 99%
“…It was licensed based on non-inferiority of immune responses as compared with those elicited by the other U.S.-licensed quadrivalent meningococcal vaccines according to the age group [ 67 ]. In a recent exploratory phase 2 study, the immunogenicity and safety of MenQuadfi was reported to be comparable with the licensed MenACWY-TT in toddlers aged 12–24 months old, although responses to serogroups A and C differed between the vaccines [ 68 ]. Non-inferiority in terms of seroresponse rates at day 30 was demonstrated versus MenACWY-CRM in a phase 2 study in adolescents between 10 and 17 years of age [ 69 ].…”
Section: Meningococcal Polysaccharide-conjugate Vaccinesmentioning
confidence: 99%
“…This study also did not assess the levels of anti-tetanus antibodies following vaccination with MenACYW-TT; however, a phase II study of MenACYW-TT has shown an increase in anti-tetanus antibody levels following vaccination. 26 MenACYW-TT was well tolerated and immunogenic when administered to adults aged ≥56 y. If the promising data from this exploratory study are confirmed in the Phase III trial, the MenACYW-TT has the potential to be a globally available alternative for the prevention of IMD in adults aged ≥56 y in countries (including the US) where there are no conjugate vaccines licensed in this age strata.…”
Section: Discussionmentioning
confidence: 82%
“…This study also did not assess the levels of anti-tetanus antibodies following vaccination with MenACYW-TT; however, a phase II study of MenACYW-TT has shown an increase in anti-tetanus antibody levels following vaccination. 26 …”
Section: Discussionmentioning
confidence: 99%